Total and regional fat‐to‐muscle mass ratio measured by bioelectrical impedance and risk of incident type 2 diabetes. Issue 6 (30th September 2021) - Wang, Ningjian; Sun, Ying; Zhang, Haojie; Chen, Chi; Wang, Yuying; Zhang, Jihui; Xia, Fangzhen; Benedict, Christian; Tan, Xiao; Lu, Yingli
Abstract: Background: The fat‐to‐muscle mass ratio (FMR) might be an indicator to assess type 2 diabetes risk independent of general obesity. However, no longitudinal studies have explored the extent to which total and regional FMRs may confer risks. We aimed to measure the sex‐specific associations between FMRs of the arm, leg, trunk and whole body and incident type 2 diabetes. Methods: A total of 464 817 participants (207 286 men and 257 531 women, mean age 56.5 ± 8.2 and 56.2 ± 8.0 years old, respectively) free of diabetes at baseline were included in this prospective cohort study with UK Biobank data. Fat mass and muscle mass were estimated using a bioelectrical impedance assessment device (Tanita BC 418MA). FMR was calculated as fat mass divided by muscle mass in corresponding body parts (total body, arm, leg and trunk). Cox proportional hazard models were used to estimate the aforementioned associations among men and women. Interaction analyses were performed between FMRs and body mass index (BMI) categories (BMI < 25 kg/m 2 and BMI ≥ 25 kg/m 2 ). Results: Over the median 11.0 years (5 057 534 person‐years) of follow‐up, we documented 11 618 cases of type 2 diabetes. There was a significantly positive association between total and regional FMR and incident type 2 diabetes, even after adjusting for BMI and other covariates. Compared with other body parts, FMRs of the whole body and leg showed the strongest relationship among men and women, respectively (hazard ratio per 1 SD, 95% confidence interval: 1.67, 1.55–1.80; 1.45, 1.39–1.53). A significant interaction ( P for interaction < 0.001) between BMI category and FMRs of different body parts was observed. In the stratified analysis by BMI category and tertiles of FMRs, overweight/obese individuals with a high FMR tertile tended to have the highest hazard ratio, ranging from 5.91 to 7.94 in whole body and regional areas. Conclusions: In this large prospective study, higher total and regional FMRs were associated with a higher risk of developing type 2 diabetes, independent of BMI. This association was markedly strengthened in participants with BMI ≥ 25 kg/m 2 .